Efficacy of a micronized, nanocrystal fenofibrate formulation in treatment of hyperlipidemia in dogs. (6th June 2021) - Munro, Matthew J. L.; Hulsebosch, Sean E.; Marks, Stanley L.; Gilor, Chen
Abstract: Background: Safe, effective, and readily available drug therapies are required for the management of hyperlipidemia and its associated complications in dogs. Objectives: To investigate the efficacy of a micronized, nanocrystal formulation of fenofibrate (Tricor) in the treatment of hyperlipidemia in dogs. Animals: Ten client‐owned dogs with primary (n = 7) and secondary (n = 3) hyperlipidemia. All dogs had hypertriglyceridemia at baseline; 3 dogs also had hypercholesterolemia. Methods: Prospective dose‐escalation study. Dogs were treated with fenofibrate orally once daily in up to 3 cycles of 21 days each. Fenofibrate dose was increased at the end of each cycle if hypertriglyceridemia persisted and adverse effects were not documented. Complete blood count, biochemistry, and urine protein:creatinine ratio were collected serially. Baseline (T0) parameters were compared to time of maximal reduction in serum triglyceride concentrations (T1) and reported as median (range). Results: Triglycerides normalized in all dogs (T0 = 662 mg/dL [189‐2391]; T1 = 113 mg/dL [81‐132]; P = .002). Fenofibrate dose at T1 = 6.4 mg/kg PO q24h (range, 2.2‐13.5). T1 was achieved at 3 (n = 4), 6 (n = 4), and 9 (n = 2) weeks. Serum cholesterol concentrations decreased in 9 of 10 dogs. Quiet demeanor and firm stools in 1 dog were the only reported adverse reactions. Fenofibrate administration resulted in a significant reduction in median alkaline phosphatase activity ( P = .049). Conclusions and Clinical Importance: Over 21 to 63 days, TriCor was effective in the management of primary and secondary hyperlipidemia in dogs.